(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
The Indonesian Conditional Cash Transfer Program or Program Keluarga Harapan (PKH) is a program to improve the quality of life including food consumption quality. This study aims to determine the quality of family consumption food, effect of PKH to improve the quality of life and nutritional status of toddlers in PKH families. This research is a cross-sectional study involving 90 families in Harau sub-district, Limapuluh Kota Regency, West Sumatra in March-June 2021. The quality of family food consumption is measured using the Household Dietary Diversity Score (HDDS) questionnaire. The results in this study were that 97.8% of the subjects had a high diversity score (more than 6 types of food groups) and 86% of the subjects ackonwladged PKH improved their quality of life. Unfortunetly, in PKH families, there are 27.8% of toddlers with stunting and 3.3% of toddlers with malnutrition. To be concluded that PKH improves the quality of life and quality of food consumption but longterm evaluation needed to asses effect PKH to stunting.